Pemenuhan Jaminan Kecelakaan Kerja Dan Jaminan Kematian Bagi Anak Buah Kapal (Studi Putusan MA Nomor 447 K/PDT.SUS-PHI/2024) - Siahaan, Gabriella; Agusmidah, Agusmidah; Mulhadi, Mulhadi (Magister Kenotariatan, Universitas Jambi, 2026)
This study examines the legal responsibility of fisheries companies in fulfilling occupational accident and death insurance for crew members (ABK) in the fisheries sector, which has a high risk of fatal accidents and death. Through Supreme Court Decision Number 447 K/Pdt.Sus-PHI/2024, it is clear that the company was negligent in registering crew members with the BPJS Employment program, thus raising the issue of who is responsible for protecting crew members who experience work accidents resulting in death. This study uses a normative juridical method with a statute approach and a case approach, with secondary data obtained through literature studies and document studies of primary, secondary, and tertiary legal materials. The results of the study indicate that the fisheries company was negligent as an employer in providing protection for crew members because it did not register their participation in the BPJS Employment program as regulated in Article 99 of the Manpower Law. Therefore, the judge's consideration requiring the company to pay compensation is in accordance with the law. However, in addition to civil liability, the company should also be subject to administrative sanctions as regulated in Article 17 of Law Number 24 of 2011 concerning BPJS.